2020
DOI: 10.3390/ani10040646
|View full text |Cite
|
Sign up to set email alerts
|

Can the Presence of Ovarian Corpus Luteum Modify the Hormonal Composition of Follicular Fluid in Mares?

Abstract: The hypothesis of this study was to investigate if the presence of corpus luteum (CL) in one ovary could modify the hormonal content of follicular fluid (FF) in the follicles. Sixty ovaries were taken after the slaughter of 30 clinically healthy mares. In relation to the sizes, the follicles were classified into three different categories, as small (20–30 mm), medium (31–40 mm) and large (≥41 mm). Blood samples were collected from the jugular vein of mares before their slaughter, and then the FF samplings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…The cyclic activity of the ovary is mainly influenced by reproductive hormones [ 48 , 49 ]; under the stimulation of FSH and LH, the follicles undergo primary, secondary, and antral stages, and only a few of them reach the pre-ovulatory stage [ 50 ]. After superovulation treatment in the present study, we found that there was no significant difference in the concentrations of FSH and LH in jugular vein serum between lambs and adult sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclic activity of the ovary is mainly influenced by reproductive hormones [ 48 , 49 ]; under the stimulation of FSH and LH, the follicles undergo primary, secondary, and antral stages, and only a few of them reach the pre-ovulatory stage [ 50 ]. After superovulation treatment in the present study, we found that there was no significant difference in the concentrations of FSH and LH in jugular vein serum between lambs and adult sheep.…”
Section: Discussionmentioning
confidence: 99%
“…All year round, the maturation rate of equine oocytes was directly correlated with follicle size (Hinrichs and Schmidt, 2000). The follicular development in mares influences the follicular metabolites, electrolytes (Satué et al 2019) and steroid hormones (Satué et al 2020). Interestingly, FF components, related to the oocytes developmental competence, have been clearly described in cows (Annes et al 2019), camels (El-Shahat et al 2018, goats (Junior et al 2018), and sows (Bertoldo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, steroid hormones in follicular fluid dynamically change according to the presence or not of CL in the ovary of mares. Satué et al (2020) found in the follicular fluid of large and medium follicle sizes, E2 concentrations were significantly higher than in non-CL groups. Also, testosterone and androstenedione were significantly increased in larger follicles in the non-CL groups; also, intrafollicular Effect of exogenous progestogen treatment was confirmed on P4 plasma concentration produced by CLs, at D8 after ovulation, and on the average diameter of the pre-ovulatory follicle.…”
Section: Discussionmentioning
confidence: 64%